Recycling of plastic waste polyethylene terephthalate (PET) as a modifier in asphalt mixture: study of Creep-Recovery at Low, Medium, and Hot Temperatures - Amine Bekhedda; Mohammed Merbouh (Fracture and Structural Integrity)
One environmental problem in most countries is the huge quantities of plastic waste, which has different types of polymers such as polyethylene terephthalate (PET), polypropylene (PP)., These plastics become a problem because of their non-biodegradability, toxicity, etc. The recovery of plastic waste in pavements has become an ecological technique that contributes to the preservation of natural resources. In this study, PET waste was used as an additive for hot mix asphalt at two sizes (2.50 to 1.25 mm, and 0.315 to 0.160 mm) and three contents (3%, 5%, and 7% by weight of binder), PET modified mixes creep-recovery behavior was tested by four points bending test and compared with control mix (without PET waste) at three different temperatures (0, 25 and 50C), were added directly to the mixture as the method of dry process. The results showed that the addition of PET waste yields better results that which could increase the asphalt bituminous resistance against permanent deformation and a clear rigidity improvement in the various temperature because it's more thermally stable and can limit the degradation risks of the bituminous mixtures compared to the control mixture. Further, can be prepared an eco-friendly road construction with less material cost.